Integrating ESG, AI, and Financial Strategies in Banking: Advancing Sustainable Innovation and Risk Management - Morina, Fisnik; Dinaj, Saimir (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This paper analyzes the integration of environmental, social, and governance (ESG) sustainability strategies, artificial intelligence (AI), and financial strategy in the banking industry to advance sustainable innovation and risk management. This study explores the impact of these factors on improving banking performance and risk diversification, particularly emphasizing the correlation between sustainability best practices and various financial benefits. The scientific methodology used in this paper is qualitative. It is based on the explanation and analysis of three case studies: Nova Ljubljanska Banka (NLB) in Slovenia, Erste Group Bank AG in Austria, and Bank of Valletta (BOV) in Malta. The data for these case studies were collected from official reports, documents, and other relevant sources. Also, this data was analyzed through a comparative matrix of ESG and AI performance in the studied banks. The results of the study show that the integration of ESG and AI improves financial performance and has positive effects on the sustainability and transparency of banking operations. The practical implications of this study are that banks, in general, can benefit from implementing these strategies to strengthen their competitive advantages in sustainable economic development.